Taxonomic Revision of Pinus fujiii (Yasui) Miki (Pinaceae) and Its Implications for the Phytogeography of the Section Trifoliae in East Asia. - Toshihiro Yamada; Mariko Yamada; Minoru Tsukagoshi (PLoS ONE, 2015)
Pinus trifolia Miki 1939 (Pinaceae) was originally proposed based on seed cones from the upper Miocene of Aichi and Gifu Prefectures, central Japan. However, before the publication of P. trifolia, a different name (Pinus fujiii (Yasui) Miki) was given to a female cone with the same morphology. On the other hand, P. fujiii auct. non (Yasui) Miki has been used for seed cones with different morphologies from Yasui's holotype, i.e., apophyses arranged in 5:8 parastichies and a perexcentromucronate slightly-pointed umbo. As a result of re-examination on the Miki and Yasui specimens, we concluded that P. trifolia was a synonym for P. fujiii and proposed here Pinus mikii sp. nov. for cones assigned to P. fujiii auct. non (Yasui) Miki. We also emended the diagnosis of P. fujiii based on these specimens. Pinus fujiii is characterized by a large female cone in which the apophyses with a centromucronate prickle-like umbo are arranged in 8:13 parastichies, and deciduous seed wings. These characters suggest that P. fujiii belongs to the section Trifoliae of the subgenus Pinus, which is now restricted to North and Central America and the Caribbean islands. Fossil data suggest that the P. fujiii lineage firstly appeared in Japan around the Eocene/Oligocene boundary. We speculate that the P. fujiii lineage might have moved southward to Japan from a refugium located elsewhere in high-latitude areas in response to the late Eocene cooling event, as occurred with other Trifoliae species in North America.